Asuhan Keperawatan pada Ny.Z Dengan Demam Thypoid - Tiara abdul novitria; Yessi, Hilma; Marni, Linda; Asmaria, Mike (Jurnal Keperawatan Medika, 2025)
According to the World Health Organization (WHO), it is estimated that every year worldwide there are between 11-21 million cases of typhoid fever with a death incidence of 128,000 (12.8%) to 161,000 (16.1%). Based on data on typhoid fever cases at Aisyiyah Pariaman Hospital in 2024, typhoid fever ranks fourth in the most common diseases, around 237 (23.7%) cases. The purpose of the study is to be able to carry out nursing care for patients with typhoid fever by including assessment, diagnosis, intervention, implementation, evaluation, and documentation. The study was conducted in the Musdalifah room of Aisyiyah Pariaman Hospital on February 18 to February 22, 2025 with one patient, Mrs. Z, aged 40 years, using a case study method with data collection techniques by means of observation, interviews, and physical examination. There are five nursing problems, namely hyperthermia, acute pain, risk of nutritional deficits, nausea and sleep pattern disorders. On the third day, the diagnosis of hyperthermia and the risk of nutritional deficit were confirmed, with the patient's body temperature normalizing and appetite improving. On the fourth day, the diagnosis of nausea and sleep disturbance was confirmed, as indicated by a reduction in nausea and vomiting, and a decrease in insomnia. On the fifth day, the diagnosis of acute pain was confirmed, with a decrease in the pain scale. It is hoped that the patient and family will maintain environmental and dietary hygiene, consume healthy, hygienic, and nutritious food, and get enough rest to prevent typhoid fever from recurring.